Lecturer’s Code-Switching in the EFL Classroom of Arabic Language and Literature - Renggi Vrika; Melisa Rezi (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
In teaching and learning languages, it is common to use code-switching. Code-switching help speaker and hearer share the ability to speak more than one language. This research was focused on the code-switching that was done by the lecturer, the most common type that appeared in the classroom interaction and the function of the code-switching found in the analysis. Descriptive qualitative research was applied in this research which the data got from the interaction of the lecturer and students in the classroom in teaching and learning English for Arabic students. Based on the analysis, in the classroom interaction, the three types of code-switching was found; tag-switching, inter-sentential switching and intra-sentential (Romaine, 1995). The most common type found in the interaction was intra-sentential switching. The used of code-switching in the classroom interaction was to improve language skills, give clarification, emphasis the topic, and make good relation with interlocutor that was the Arabic students. Both teachers and students in this situation hold positive attitudes in doing code switching.